2022
DOI: 10.1021/acs.jafc.2c01513
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin Ameliorates Hyperuricemia by Regulating Renal Uric Acid Excretion via the PI3K/AKT Signaling Pathway and Renal Inflammation through the NF-κB Signaling Pathway

Abstract: Hyperuricemia characterized by high serum levels of uric acid (UA, >6.8 mg/dL) is regarded as a common chronic metabolic disease. When used as a food supplement, naringenin might have various pharmacological activities, including antioxidant, free-radical-scavenging, and inflammation-suppressing activities. However, the effects of naringenin on hyperuricemia and renal inflammation and the underlying mechanisms remain to be elucidated. Here, we comprehensively examined the effects of naringenin on hyperuricemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Once these transporters are dysfunctional, the uric acid metabolic system will be disrupted, contributing to hyperuricemia. 31 In this study, TE showed an XOD inhibitory effect in HN rats and reversed the dysregulated expression of the uric acid transporters. Consistently, TE promoted the excretion of uric acid.…”
Section: ■ Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Once these transporters are dysfunctional, the uric acid metabolic system will be disrupted, contributing to hyperuricemia. 31 In this study, TE showed an XOD inhibitory effect in HN rats and reversed the dysregulated expression of the uric acid transporters. Consistently, TE promoted the excretion of uric acid.…”
Section: ■ Discussionmentioning
confidence: 52%
“…Uric acid transporters such as GLUT9, OAT3, and ABCG2 are commonly located in the human intestine and the renal proximal tubule. Once these transporters are dysfunctional, the uric acid metabolic system will be disrupted, contributing to hyperuricemia . In this study, TE showed an XOD inhibitory effect in HN rats and reversed the dysregulated expression of the uric acid transporters.…”
Section: Discussionmentioning
confidence: 64%
“…This process is referred to as lipid raft-dependent redox signaling, which profoundly affects cell physiopathology in various mammalian cells . Naringenin can inhibit TLR4/NF-κB and effectively alleviate the inflammatory response, which shows a protective role in the gut. Here, we provide evidence that the modulation of TLR4/NF-κB by naringenin requires subcellular TLR4 translocation, which is also controlled by lipid raft redox signaling. Therefore, our findings indicate that the lipid raft is a key point and is part of a highly important signaling mechanism that is involved in naringenin-mediated regulation of antioxidation and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 74%
“…UA excretion occurs mainly in the kidney and to a lesser extent in the intestine through metabolism by intestinal bacteria (Yang et al., 2023). The renal excretion pathway of UA consists of four main components, namely filtration‐reabsorption‐secretion‐post‐secretion reabsorption.…”
Section: Discussionmentioning
confidence: 99%